Developing quality indicators for learning with care - Graham Connelly (Scottish Journal of Residential Child Care)
As part of its response to the report, the Scottish Executive commissioned work to develop training and other support materials aimed at improving educational outcomes for looked after children and young people. The project was undertaken by a partnership led by the Scottish Institute for Residential Child Care (SIRCC), and including the British Association for Adoption and Fostering, Save the Children, Who Cares? Scotland and the Faculty of Education in the University of Strathclyde. The products of the project included a training pack (Hudson et al., 2003), an information booklet (Connelly, McKay and O'Hagan, 2003) and an independent report prepared by Who Cares? Scotland and Save the Children (Ritchie, 2003).The project team was also asked to undertake the development of quality indicators in response to Recommendation 7 in the Learning With Care report:'As part of their quality assurance procedures local authorities should undertake an audit of their residential units to assess how far they are educationally rich environments and, where shortcomings are found, make plans to take appropriate action' (ibid., p.7).